The European common market : an analysis of commercial policy - Frank Isaiah; Allison, John R. (London : Stevens & Sons Ltd, 1961)
The launching of the European Common Market has touched off intensive interest in arrangements for regional economic integration elsewhere in the world.
gp. 24/01/2019
Loans
Keywords: United States; Europe